Diseño de medidas de control para la actividad de atención domiciliaria en BHC (2021)
The work of home caregivers has had its boom recently in the world, although much is still unknown about the activities associated with this work, companies are beginning to pay more and more attention to the labour conditions in which their employees are working, prioritizing their productivity without affecting the welfare of workers who develop such activities. One of the main affectations suffered by home caregivers is associated with musculoskeletal disorders, which are associated with repetitive movements and movements of heavy loads without the correct use of proper postures; in this work we will know the main causes associated with the appearance of these disorders, the affectations suffered by workers and ways to prevent them.